2001
DOI: 10.1002/1522-2683(20017)22:11<2343::aid-elps2343>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of late-infantile neuronal ceroid lipofuscinosis: A new sensitive method to assay lysosomal pepstatin-insensitive proteinase activity in human and animal specimens by capillary electrophoresis

Abstract: Batten disease, or human late-infantile neuronal ceroid lipofuscinosis (LINCL) is a familiar progressive degenerative disease affecting children, caused by a deficiency of a lysosomal proteinase (tripeptidyl peptidase I, TPP-I) and characterized by the accumulation of autofluorescent storage bodies in the brain and other tissues of the body. Current methodology used to diagnose this disease needs to be improved in order to have less invasive techniques with higher resolution and shorter assay time. In this rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This study also showed the presence of enzyme activity in various animals having NCL-like neurodegenerative symptoms rendering them unsuitable for being a model for classical LINCL (30). Furthermore, using a highly sensitive capillary electrophoresis technique, Viglio et al (8) reported that lymphocytes from patients affected with LINCL exhibited TPP1 activity, although at low levels (in a range between 0.1 and 0.8 milliunits/mg). These findings about the presence of residual enzymatic activity in LINCL patients are very interesting as they indicate the presence of at least a few copies of the functional gene in the system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also showed the presence of enzyme activity in various animals having NCL-like neurodegenerative symptoms rendering them unsuitable for being a model for classical LINCL (30). Furthermore, using a highly sensitive capillary electrophoresis technique, Viglio et al (8) reported that lymphocytes from patients affected with LINCL exhibited TPP1 activity, although at low levels (in a range between 0.1 and 0.8 milliunits/mg). These findings about the presence of residual enzymatic activity in LINCL patients are very interesting as they indicate the presence of at least a few copies of the functional gene in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse Primary Astrocytes-There have been reports that residual TPP-I activity can be found in patients indicating that a few copies of normal Cln2 gene are left in patients affected with LINCL (8,9,30,31). We examined if FDA-approved lipid-lowering drugs like gemfibrozil and fenofibrate were capable of up-regulating the expression of TPP1 in brain cells.…”
Section: Fibrate Drugs Up-regulate Tpp1 Mrna and Protein Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic late-infantile form of NCL (LINCL) is characterized by mutations in the Cln2 gene, which encodes a lysosomal enzyme TPP1. Several reports have indicated that residual activity of TPP1 is retained in LINCL (3,20,21) prompting a new field of research directed towards enhancing the function of residual TPP1 under disease scenario. In this study, we demonstrate that HDMB, an endogenous ligand of PPARα, can upregulate TPP1 expression and activity in mouse neuronal cell line and primary brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at present, there is a requirement for novel, less invasive treatment options for LINCL. Studies have suggested that residual TPP1 activity is retained in LINCL patients, suggesting that a limited number of functional copies of the Cln2 gene are present in these patients (3,20,21). Therefore, drugmediated therapeutic strategies targeted towards augmenting the expression and residual activity of TPP1 could be of potential benefit for LINCL treatment.…”
Section: Introductionmentioning
confidence: 99%